Media Booklet Gizi Seimbang dan Status Fungsional Keluarga Efektif dalam Meningkatkan Pengetahuan Ibu Balita - Nafilah Nafilah; Eliyana Eliyana (JURNAL RISET GIZI, 2025)
Introduction: Families have various functions that must be carried out effectively, one of which is the function of family care. Maintaining family health begins with providing balanced and adequate nutrition for all family members, especially for toddlers who are still in the golden period of growth and development. Unbalanced nutrition triggers health problems for toddlers and can even cause death. The low knowledge and awareness of mothers towards the fulfillment of balanced nutrition results in the emergence of negative behavior in mothers and families.Purpose: This study aims to determine the effectiveness of using booklet media on changes in mothers knowledge about balanced nutrition and family functions.Methods: A quasi-experimental design with pretest-posttest group involved 20 mothers as respondents who were divided into two groups. This study was conducted in Truko Village using a questionnaire on knowledge of balanced nutrition and family functional roles. Data were analyzed using univariate and bivariate where paired sample t-test was used to measure the mean difference in knowledge related to family functional role. Furthermore, the Wicoxon test was used to analyze differences in mean knowledge of mothers about balanced nutrition.Results: Based on the results of the analysis, there was a significant difference in both mothers' knowledge about the functional role of the family and about the functional role of the family before and after being given education using booklet media. This means that the use of booklets as educational media is proven effective.Conclusion: The better the knowledge, the more positive the mother's behavior related to the fulfillment of nutrition and the implementation of family functions. Therefore, health promotion efforts need to be a shared responsibility so that the level of public health, especially toddlers, can reach an optimal level.Â